GLP‐1 Receptor Agonist Exenatide Attenuates the Detrimental Effects of Obesity on Inflammatory Profile in Testis and Sperm Quality in Mice. (19th August 2015) - Zhang, Erhong; Xu, Fen; Liang, Hua; Yan, Jinhua; Xu, Haixia; Li, Zhuo; Wen, Xingqiao; Weng, Jianping
<x xml:space="preserve">Abstract</x> Problem Male obesity has been linked to subfecundity. This study is to investigate the effects of GLP‐1 receptor (GLP‐1R) agonist exenatide on sperm quality in high‐fat diet (HFD)‐induced obese mice. Method of study After 12 weeks of chow diet (CD) or HFD challenge, mice on HFD were allocated to either saline or exenatide (24 nmol/kg/day) interventions for 8 weeks. Sperm quality and the inflammatory profile of testis were compared among three groups. Results Obesity reduced the quality of sperm and changed the inflammatory profile characterized by increased mRNA expression levels of TNF‐α, MCP‐1, and F4/80 in testis. Exenatide intervention reduced the expression of pro‐inflammatory cytokines and improved the quality of sperm. Conclusion HFD‐induced obesity leads to the impairment of sperm quality and increased inflammation of testis in mice, and the abnormal physiology can be attenuated by exenatide treatment. Exenatide treatment may bring additional profits to obese and diabetes men by improving sperm function.